Impact of Print Speed and Nozzle Temperature on Tensile Strength of 3D Printed ABS for Permanent Magnet Turbine Systems - Wirawan, Wirawan; Firmansyah, Hilmi Iman; Adiwidodo, Satworo; Mustapa, Mohammad Sukri (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Operational parameters must be integrated into turbine systems' main components, which are determined by turbine systems' functional requirements. The need for producing component designs more effectively raises the possibility of using additive manufacturing. The study focuses on the optimization of the mechanical properties of the principal components of magnetic turbines manufactured with 3D printers using Acrylonitrile Butadiene Styrene (ABS), by changing the temperature and speed of the nozzle. The approach consisted of modeling a standard test piece in CAD software and producing ABS-based test pieces using a 3D printer with print speeds of 50, 70, 90, and 110 mm/s and temperatures of 230, 240, 250, and 260 °C. The tensile properties of the samples were determined according to ASTM D638-14 Type I, and the results reveal a consistently greater tensile strength for the parts with high nozzle temperatures of approximately 250 °C and lower print speeds of 50 and 70 mm/s. At higher speeds of 90 and 110 mm/s, though the nozzle temperature has little effect on tensile strength, suggesting that the effect of other parameters is more significant. Whatever the print speed, at higher nozzle temperature (250℃), average tensile strength was improved. Control of nozzle temperature is paramount in increasing tensile strength in the 3D printing process performed at low speeds. Also, the average tensile strength is consistent and normalized. For all print speed values, a 250℃ nozzle produces consistently higher average tensile strength than a 235℃ nozzle. Analysed the parameters for print speed and nozzle temperature, providing optimal results for stronger and more reliable parts for use in turbines.